Impact of matrix metalloproteinase 9 rs3918242 genetic variant on lipid-lowering efficacy of simvastatin therapy in Chinese patients with coronary heart disease - Yuanyuan Xu; Yan Wang; Jixin Zhi; Lichun Qi; Tong Zhang; Xueqi Li (BMC, 2017)
Abstract Background Genetic variation of matrix metalloproteinase 9 (MMP-9) gene polymorphism has been suggested to modulate coronary heart diseases (CHD), yet the underlying mechanisms are not well understood. Methods We investigated the association of MMP9 rs3918242 single nucleotide polymorphism with inflammation and lipid-lowering efficacy after simvastatin treatment in Chinese patients with CHD. Fasting serum lipid profile and plasma inflammatory mediators were determined at baseline in 264 patients with CHD and 186 healthy control subjects, and after HMG-CoA reductase inhibitor simvastatin treatment (20 mg/day) for 12 weeks in CHD subjects. Results We found that plasma MMP-9, TNF-α and IL-10 levels were significantly elevated in patients with CHD compared to control subjects before treatment. The plasma MMP9 in CHD patients carrying rs3918242 CC, CT and TT genotypes were comparable. Interestingly, CHD patients carrying TT genotype had significantly higher level of triglyceride (TG) and low-density lipoprotein cholesterol (LDL-C) than those carrying CC genotype (P <0.05). Simvastatin treatment significantly reduced LDL-C, TG and plasma inflammatory mediator levels in CHD patients. The reduction of LDL-C upon simvastatin therapy was significantly greater in patients carrying TT genotype than those carrying CC genotype (P <0.05). Conclusions MMP9 rs3918242 TT genotype is associated with elevated serum TG and LDL-C, and enhanced LDL-C-lowering response upon simvastatin treatment in Chinese patients with CHD. Clinical trial registration This study was retrospectively registered at Chinese Clinical Trial Registry (Registration number: ChiCTR-ROC-17010971 ) on March 23rd 2017.